Investigation on the interaction between nanocarriers and functional compounds of flavonoids - Caruso, I. P. [UNESP]; Vilegas, W. [UNESP]; Souza, F. P. [UNESP]; Fossey, M. A. [UNESP]; Cornelio, M. L. [UNESP]; Narain, N. (Int Soc Horticultural Science, 2018)
Studies have suggested that a diet rich in functional foods containing flavonoids provides benefits to human health for anti-inflammatory, antioxidant, antibacterial, and anticancer activities. These compounds are usually present in fruits, vegetables and beverages. Human Serum Albumin (HSA) is a predominant carrier protein in blood plasma. The exceptional capacity of HSA to interact with many molecules makes this protein an important regulator of intercellular fluxes. In this work, HSA was used as a model for the study of nanocarrier-flavonoid interaction. The flavonoids investigated were Rutin (RU) and Guaijaverin (GUA). For analytical studies a combination of steady-state fluorescence spectroscopy and molecular modelling calculations were employed. The fluorescence quenching results indicated that the flavonoids binding near residue Trp214, which is localized in the subdomain IIA of HSA. The quenching mechanism is static which indicates the formation of the HSA-flavonoid complexes. The Gibbs free energy changes of both complexes were negative which characterize spontaneous reactions. The molecular modelling results for binding of RU and GUA with HSA are in accordance with the fluorescence spectroscopy data.
Keywords: flavonoids; fluorescence spectroscopy; molecular modelling; nanocarrier